Does Educational Marginalization Mediate the Path from Childhood Cumulative Risk to Criminal Offending? - Solomon, Starr J. (Journal of developmental and life-course criminology, 2017)
Early exposure to multiple risk factors is known to predict involvement in criminal offending. The purpose of this study was to examine the processes responsible for this association. Specifically, the focus was on the capacity of adolescent educational experience to mediate the effect of childhood cumulative risk (CCR) on criminal offending, net of expected continuity in antisocial propensity, and behavior.